Mitochondrial energy deficiency leads to hyperproliferation of skeletal muscle mitochondria and enhanced insulin sensitivity - Morrow, Ryan M. (Proc Natl Acad Sci U S A, 2017)
Diabetes is associated with impaired glucose metabolism in the presence of excess insulin. Glucose and fatty acids provide reducing equivalents to mitochondria to generate energy, and studies have reported mitochondrial dysfunction in type II diabetes patients. If mitochondrial dysfunction can cause diabetes, then we hypothesized that increased mitochondrial metabolism should render animals resistant to diabetes. This was confirmed in mice in which the heart–muscle–brain adenine nucleotide translocator isoform 1 (ANT1) was inactivated. ANT1-deficient animals are insulin-hypersensitive, glucose-tolerant, and resistant to high fat diet (HFD)-induced toxicity. In ANT1-deficient skeletal muscle, mitochondrial gene expression is induced in association with the hyperproliferation of mitochondria. The ANT1-deficient muscle mitochondria produce excess reactive oxygen species (ROS) and are partially uncoupled. Hence, the muscle respiration under nonphosphorylating conditions is increased. Muscle transcriptome analysis revealed the induction of mitochondrial biogenesis, down-regulation of diabetes-related genes, and increased expression of the genes encoding the myokines FGF21 and GDF15. However, FGF21 was not elevated in serum, and FGF21 and UCP1 mRNAs were not induced in liver or brown adipose tissue (BAT). Hence, increased oxidation of dietary-reducing equivalents by elevated muscle mitochondrial respiration appears to be the mechanism by which ANT1-deficient mice prevent diabetes, demonstrating that the rate of mitochondrial oxidation of calories is important in the etiology of metabolic disease.